A Case Report of a Free Gingival Graft Done to Rectify Gingival Recession - Shah, Rahul; Shah, Chirag; Shah, Kunjal Chirag; Shah, Bhavika; Lakshmi, Praveena (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Gingival recession is associated with functional problems such as dentinal hypersensitivity and root caries. This case report describes treatment of gingival recession with free gingival graft technique. Free gingival grafting was done in relation to 31. Split-thickness flap was elevated in the region of 31. The area to be taken for grafting was selected between first and second premolar. The graft was placed on the recipient bed and suturing was done. Complete recession coverage was observed. Results of free gingival grafting show fairly acceptable results in terms of tissue gain suggesting free gingival graft as a viable option.